Design and Implementation of a Solar-Powered IoT Smart Fish Feeder for Sustainable Freshwater Aquaculture - Micko Tomas; Baik Budi; Khadlel Muhammad Romiz (Indonesian Society of Applied Science, 2026)
The utilization of solar energy in aquaculture automation still encounters challenges related to energy efficiency, stability, and adaptive control within IoT-based systems. This research presents the design and implementation of a solar-powered IoT Smart Fish Feeder, developed to enable adaptive feeding schedules with optimized power management. The system is composed of a 100 Wp solar panel, a 25 A MPPT charge controller, a 14.8 V lithium battery, a 2P DC MCB (440 V/25–16 A), and an APZEM-017 ModBus DC wattmeter, integrated with a DC–DC Boost Converter to regulate power delivery for the feeder prototype. Experimental tests were conducted to evaluate solar energy performance under real environmental conditions, focusing on parameters such as voltage, current, power output, and energy conversion efficiency. Results demonstrated that the solar panel achieved an average conversion efficiency of 87.2%, the MPPT controller maintained an efficiency of 95%, the battery system reached a charge–discharge efficiency of 90.4%, and the DC–DC converter operated at 92% efficiency, resulting in an overall system efficiency of 68.8%. The system maintained voltage stability within ±2% and was capable of autonomous 24-hour operation without external power. Compared to previous studies that lacked solar–IoT integration and adaptive control, this prototype provides a novel and energy-efficient solution for sustainable aquaculture. The findings confirm that the proposed design enhances renewable energy utilization, operational reliability, and environmental sustainability in innovative aquaculture applications.